Diallyl Disulfide prevention of Cis-diammine Dichloroplatinum–induced Nephrotoxicity and Leukopenia in rats: potential adjuvant effects - Chiarandini Fiore, Jessica Paola (2008)
Cisplatin (CisPt) is an effective chemotherapeutic agent against several human cancers, but it produces important nephrotoxicity, leukopenia, and mortality. In this work, we report initial results on the potential ability of diallyl disulfide (DADS) to block these toxicities without compromising chemotherapy. Male Sprague Dawley rats were used (control, DADS, CisPt, and CisPt/DADS). CisPt was administered sc as a single dose (10.5 mg/kg) in saline. DADS was given daily intragastrically in olive oil (292.5 mg/kg) 1 h before CisPt administration the first day and 146.25 mg/kg during the next 3 days. The animals were sacrificed at the fifth day after CisPt administration. DADS significantly decreased CisPt-induced nephrotoxicity as evaluated by histology and by seric urea (CisPt: 11.05 ± 3.59; CisPt/DADS: 6.53 ± 1.74) and creatinine (CisPt: 24.74 ± 3.03; CisPt/DADS: 14.83 ± 2.07). DADS also decreased leukopenia (CisPt: 13.5% and CisPt/DADS: 43.4% respect the control), and mortality (CisPt: 50%; CisPt/DADS: 29%). DADS showed ability to interact with reactive oxygen species (H2O2, hydroperoxides, OH•) and with iron. DADS treatment does not change Platinum levels in kidney (CisPt: 15.2 ± 5.1; CisPt/DADS: 13.9 ± 4.5). Because DADS is known to inhibit cellular replication and to promote apoptosis of tumor cells, results suggest that DADS merit to be tested as a potential coadjuvant of CisPt chemotherapy in tumor-bearing animals.